2017
DOI: 10.1021/acs.iecr.6b04463
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Oxide Removal from Simulated Flue Gas by UV-Irradiated Sodium Chlorite Solution in a Bench-Scale Scrubbing Reactor

Abstract: Ultraviolet irradiated sodium chlorite (UV/NaClO2) solution was introduced to remove nitrogen oxide (NO x ) from simulated flue gas in a bench-scale scrubbing reactor. Effects of UV irradiation time, NaClO2 concentration, NO inlet concentration, pH value, and O2 concentration were investigated separately. Results showed that NaClO2 solution with UV pretreatment achieved a remarkable promotion in NO x removal efficiency. The ClO2 produced from photodecomposition of NaClO2 in aqueous solution substantially impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Generally, the increase of molar ratio would promote the mass-transfer driving force of NO, which improves the oxidation and absorption of NO. However, NO concentration in the gas was relatively much higher than that of the NaClO2 mist, it seemed to be reasonable to obtain a declining NO removal rate [39]. As shown in Figure 7, when the NO concentration changed from 100 ppm to 300 ppm, the NO removal efficiency for 0.01 mol·L −1 NaClO2 concentration decreased from 50.5% to 41.5%, but the NO removal efficiency for 0.02 mol·L −1 NaClO2 concentration increased from 72.1% to 78.8%.…”
Section: Effect Of No Concentrationmentioning
confidence: 99%
“…Generally, the increase of molar ratio would promote the mass-transfer driving force of NO, which improves the oxidation and absorption of NO. However, NO concentration in the gas was relatively much higher than that of the NaClO2 mist, it seemed to be reasonable to obtain a declining NO removal rate [39]. As shown in Figure 7, when the NO concentration changed from 100 ppm to 300 ppm, the NO removal efficiency for 0.01 mol·L −1 NaClO2 concentration decreased from 50.5% to 41.5%, but the NO removal efficiency for 0.02 mol·L −1 NaClO2 concentration increased from 72.1% to 78.8%.…”
Section: Effect Of No Concentrationmentioning
confidence: 99%
“…When the NaClO 2 concentration reached 0.02 mol/L, the increase in the NO removal rate slowed down and it was finally maintained at 68.11%. The mass transfer equation of the chemical absorption in the liquid phase [15] is:…”
Section: Effect Of Naclo2 Concentration On Denitrification Ratementioning
confidence: 99%
“…The removal rates of SO 2 and NO were 100% and 82.7%, respectively, under the optimum conditions. Yang et al [93] used ultraviolet radiation sodium chlorite (UV/NaClO 2 ) solution to remove NO x from simulated flue gas in a small scrubbing reactor. The results showed that the addition of Cu and Mn resulted in the lattice expansion and micro-strain decrease of CeO 2 -ZrO 2 , which led to the formation of oxygen vacancies.…”
Section: No X Removed By Liquid-phase Oxidationmentioning
confidence: 99%